PERAN MENU SEGO LUWUK SEBAGAI MAKANAN AUTHENTIC DI HOTEL JAMBULUWUK MALIOBORO YOGYAKARTA - Suardana, I Ketut; Auliya, Rahmat (AKPARDA, 2023)
Jambuluwuk Malioboro Hotel is one of the hotels that provides lodging services along with food and beverages. One of the food menus that are in great demand by visitors is the Nusantara Sego Luwuk menu because of the traditional flavors that make it unique. The purpose of this study was to determine the role of the Sego Luwuk menu as an authentic menu at the Jambuluwuk Malioboro Hotel, Yogyakarta. The method used in this study is a qualitative descriptive method with data collection techniques of observation, interviews, and documentation. The result of the research is that the sego luwuk menu is an authentic menu from the jambuluwuk hotel. This menu is only available at Jambuluwuk Hotels throughout Indonesia. And become a characteristic in itself. This menu can increase the number of hotel customers who enter and make this hotel much sought after for the characteristics of its sego luwuk menu.